Detection of antimicrobial resistance, pathogenicity, and virulence potentials of non-typhoidal Salmonella isolates at the Yaounde abattoir using whole-genome sequencing technique - Matchawe, C.; Machuka, Eunice M.; Kyallo, Martina M.; Bonny, P.; Nkeunen, G.; Njaci, Isaac; Esemu, S.N.; Githae, Dedan; Juma, John; Nfor, B.M.; Nsawir, B.J.; Piasentier, E.; et al. (MDPI, 2022)
One of the crucial public health problems today is the emerging and re-emerging of multidrug-resistant (MDR) bacteria coupled with a decline in the development of new antimicrobials. Non-typhoidal Salmonella (NTS) is classified among the MDR pathogens of international concern. To predict their MDR potentials, 23 assembled genomes of NTS from live cattle (n = 1), beef carcass (n = 19), butchers’ hands (n = 1) and beef processing environments (n = 2) isolated from 830 wet swabs at the Yaounde abattoir between December 2014 and November 2015 were explored using whole-genome sequencing. Phenotypically, while 22% (n = 5) of Salmonella isolates were streptomycin-resistant, 13% (n = 3) were MDR. Genotypically, all the Salmonella isolates possessed high MDR potentials against several classes of antibiotics including critically important drugs (carbapenems, third-generation cephalosporin and fluoroquinolone). Moreover, >31% of NTS exhibited resistance potentials to polymyxin, considered as the last resort drug. Additionally, ≤80% of isolates harbored “silent resistant genes” as a potential reservoir of drug resistance. Our isolates showed a high degree of pathogenicity and possessed key virulence factors to establish infection even in humans. Whole-genome sequencing unveiled both broader antimicrobial resistance (AMR) profiles and inference of pathogen characteristics. This study calls for the prudent use of antibiotics and constant monitoring of AMR of NTS.